2018
DOI: 10.1111/ans.14764
|View full text |Cite
|
Sign up to set email alerts
|

Detecting tumour response and predicting resectability after neoadjuvant therapy for borderline resectable and locally advanced pancreatic cancer

Abstract: More than half the patients undergo resection post-NAT for LAPC and BRPC. Stable, or reduction of, tumour disease may predict resectability. Reduction in tumour SUV on PET-CT and decreased tumour stiffness on EUS elastography may be potential markers of NAT response and resectability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 57 publications
0
39
0
2
Order By: Relevance
“…The results showed that the change in the tumor size after NAT on EUS was a sensitive marker for tumor response evaluation, and tumor size reduction ≥ 47% was an independent prognostic factor for OS in these patients. A systematic review from Barreto et al [ 34 ] compared the accuracy of imaging modalities to predict resectability and R0 resection for borderline or locally advanced PDAC after NAT. They showed that effective imaging evaluation allowed prediction of tumor resectability.…”
Section: Response Assessment Of Pdac After Natmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the change in the tumor size after NAT on EUS was a sensitive marker for tumor response evaluation, and tumor size reduction ≥ 47% was an independent prognostic factor for OS in these patients. A systematic review from Barreto et al [ 34 ] compared the accuracy of imaging modalities to predict resectability and R0 resection for borderline or locally advanced PDAC after NAT. They showed that effective imaging evaluation allowed prediction of tumor resectability.…”
Section: Response Assessment Of Pdac After Natmentioning
confidence: 99%
“…In a study of 129 patients with borderline PDAC, the authors found that the commonly used response evaluation criteria in solid tumors (RECIST) criteria were not suitable for evaluating tumor response after NAT, because there were few morphological changes in the imaging after treatment[ 37 ]. A systematic review reported that only a small number of patients showed tumor shrinkage after NAT (Figure 2 ), and most patients (53%-80%) had stable disease[ 34 ]. Similar results were reported by a recent study[ 38 ] that showed that the assessment of resectability by MDCT after NAT is relatively insensitive and non-specific to predict R0 resection, because MDCT cannot accurately distinguish between residual tumor and tissue scarring after tumor regression[ 39 ].…”
Section: Response Assessment Of Pdac After Natmentioning
confidence: 99%
“…The first three of these are defined by the tumour relationship to surrounding vasculature [ 81 ]. The goal of neoadjuvant treatment (NAT) in borderline resectable tumours is to allow downstaging to facilitate resection [ 18 , 82 ], and a number of trials have assessed the role of both chemotherapy and chemoradiotherapy based NAT in upfront resectable disease [ 83 , 84 , 85 ], the theory being that we would identify during treatment, those who are likely to progress rapidly and thus avoid an unnecessary and potentially morbid procedure for these patients [ 15 , 16 , 17 ]. Questions remain about the appropriate use of NAT in terms of what scenarios it should be used, for how long, and if radiotherapy has a role [ 86 , 87 ].…”
Section: The Biomechanical Pdac Microenvironmentmentioning
confidence: 99%
“…80% beträgt. Neuere wissenschaftliche Untersuchungen ebenso wie die klinische Erfahrung zeigen, dass andere bildgebende Verfahren als die hier eingesetzten, speziell die Endosonographie aber auch die PET-CT diese Rate deutlich verbessern können, besonders dann, wenn mehrere Verfahren zum Einsatz kommen [4, 5].…”
Section: Transfer In Die Praxis Von Prof Dr Hans-rudolf Raab (Oldenunclassified